Características físico químicas de vinos sueltos elaborados en bodegas del Centro Urbano de Cascas. Enero - Febrero 2016 - Armas Miranda, Lourdes Maria (2018)
The physicochemical characteristics of the loose wines elaborated in the urban center cascas were determined, for which we used 25 samples, using for this the different methods such as: picnometry (density), malligan's ebulloscope (alcoholic degree), direct weighing (extract seco), method of the American society of oenologists (total acidity), method of fehling (reducing sugars) and determination of sulfates. Of the 25 samples analyzed with respect to the organoleptic characteristics, these are within the expected ranges, such as: color, smell, taste and consistency; and for the chemical characteristics, such as: the alcoholic degree, the dry and sweet wine has a high degree compared to semi-dry wine; for density all over pass the density of water, being the highest for sweet wines; in total acidity all are within the range except for the sweet wine due to its primordial characteristic that they are sweet and finally for sulfates all are positive